Open Recognition for Impact Beyond Skills: Towards Transitions (PLA Inside Out: An International Journal on Theory, Research and Practice in Prior Learning Assessment, 2026)
Kosmio, a European company that develops digital platforms to drive sector-specific transitions, presented an integrated data architecture for making regulatory and standards compliance more efficient and effective at delivering the impact they were designed to provide. This architecture includes Open Badges as recognition vehicles not only for individuals, but also for organizations, projects, and products. Across Europe, many organizations experience what is often called "regulation fatigue": the growing burden of reporting, compliance, and certification requirements. While this bureaucracy is frequently seen as a constraint, it can also be transformed into a strategicadvantage. If implemented effectively, regulation becomes not only a driver of trust and accountability but also a competitive advantage, positioning European actors ahead of global competitors who are slower to embrace sustainability standards. However, this potential is only unlocked if regulation is made more efficient, interoperable, and transparent. Today, too many efforts are wasted in redundant reporting, fragmented data collection, and manual compliance processes. To overcome this, we must deploy the right technologies: digital tools that can automate reporting, ensure trust, and make compliance processes more fluid.At the heart of this transformation lies the need for a shared and trusted data infrastructure. A system where data can be collected once, structured according to common standards, and reused across multiple purposes. This vision is made possible by the combination of three complementary frameworks.First, Data Spaces provide the federated environments where actors can share information securely while preserving sovereignty and interoperability. Second, MRV (Measurement, Reporting, Verification) methods ensure that the data flowing through these spaces is structured, validated, and transformed into verifiable certificates of impact. Finally, Open Badges as a universally understandable way to display, communicate, and prove compliance, achievements, and impact, not only for individuals, but also for organizations, projects, and products.Traditionally, Open Recognition has mainly been applied to individuals, recognizing skills, competencies, and learning achievements. Extending this principle to companies, projects, and products creates a powerful new opportunity. Impact recognition can provide organizations with a trusted way to demonstrate compliance, showcase sustainability performance, and differentiate in global markets. Projects can use recognition to prove their contribution to transitions, while products can carry trusted marks of social or environmental value. This not only builds credibility with regulators, partners, and customers, but also creates new avenues for visibility, market access, and collective learning across ecosystems.This integrated approach turns the burden of regulation into a catalyst for innovation, trust, and competitiveness. It enables companies, territories, and coalitions not only to comply but to thrive, making compliance a driver of impact recognition and of Europe's leadership in sustainable transitions.Keywords: regulation, MRV, data spaces, impact recognition, Open Badges